2020
DOI: 10.1017/ice.2019.378
|View full text |Cite
|
Sign up to set email alerts
|

Zagros Mountains: A region in Iran with extremely high incidence of Brucellosis

Abstract: carbapenem resistance (i.e. case 2). The occurrence of these resistance mechanisms in immunocompromised cancer patients who have extensive healthcare and antibiotic exposure as well as hospital admission episodes increases the risk of infection spread in healthcare settings as well as in community (case 1). The second case shows that this resistance phenomenon can be found even in children. These cases are, to the best of our knowledge, the first reports of such infections from eastern India. Because of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The National Center for Infectious Diseases Management reported that from 1989 to 2013, the incidence of brucellosis decreased from 100 per 100,000 to 23.8 per 100,000. Brucellosis is present in all provinces of the country, but because of the occupation of livestock in the residents, it is more common in the Zagros mountains (13). The incidence of the disease shows a seasonal pattern in Iran so that it increases in spring and summer (because of mating and breastfeeding of livestock) and then decreases (14).…”
Section: Discussionmentioning
confidence: 99%
“…The National Center for Infectious Diseases Management reported that from 1989 to 2013, the incidence of brucellosis decreased from 100 per 100,000 to 23.8 per 100,000. Brucellosis is present in all provinces of the country, but because of the occupation of livestock in the residents, it is more common in the Zagros mountains (13). The incidence of the disease shows a seasonal pattern in Iran so that it increases in spring and summer (because of mating and breastfeeding of livestock) and then decreases (14).…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor-Zoonotic brucellosis is an endemic disease in many regions of the world, including the Zagros Mountains of Iran and Iraq, as Abdi et al 1 lay out in a recent article in Infection Control and Hospital Epidemiology. Abdi et al touch upon the history of farming in the Zagros Mountains to contextualize the deep time dimension of brucellosis risk for communities within this region.…”
mentioning
confidence: 99%